Phylogeographic Evidence of Crop Neodiversity in Sorghum - de Alencar Figueiredo, L. F. (Genetics Society of America, 2008)
Sorghum has shown the adaptability necessary to sustain its improvement during time and geographical extension despite a genetic foundation constricted by domestication bottlenecks. Initially domesticated in the northeastern part of sub-Saharan Africa several millenia ago, sorghum quickly spread throughout Africa, and to Asia. We performed phylogeographic analysis of sequence diversity for six candidate genes for grain quality (Shrunken2, Brittle2, Soluble starch synthaseI, Waxy, Amylose extender1, and Opaque2) in a representative sample of sorghum cultivars. Haplotypes along 1-kb segments appeared little affected by recombination. Sequence similarity enabled clustering of closely related alleles and discrimination of two or three distantly related groups depending on the gene. This scheme indicated that sorghum domestication involved structured founder populations, while confirming a specific status for the guinea margaritiferum subrace. Allele rooted genealogy revealed derivation relationships by mutation or, less frequently, by recombination. Comparison of germplasm compartments revealed contrasts between genes. Sh2, Bt2, and SssI displayed a loss of diversity outside the area of origin of sorghum, whereas O2 and, to some extent, Wx and Ae1 displayed novel variation, derived from postdomestication mutations. These are likely to have been conserved under the effect of human selection, thus releasing valuable neodiversity whose extent will influence germplasm management strategies.